Preferences between Caesarean Section and Normal Vaginal Delivery among the reproductive women in Bangladesh - Parvej, Md. Iftakhar; Tabassum, Mimma; Aktar, Nelufa (Journal of Applied Science, Engineering, Technology, and Education, 2021)
Amount of death due to pregnancy are gradually decreasing worldwide, among all of these estimated deaths, one-fifth of the maternal death recorded in southern Asia. The increasing rate of caesarean section (CS) delivery and the improved safety of surgical skill are the big reason of reduced pregnancy related mortality rate. Bangladesh has the increasing CS rate on southern Asia. This study aimed to identify the different factors affecting the increasing rate of CS in Bangladesh This cross-sectional survey was conducted between January 2020 - March 2020 among the married women at reproductive age (15-49 years age) having at least one under five years child of Dhaka and Noakhali district in Bangladesh. A questionnaire was designed to survey the preference of their delivery mode. Bivariate logistic regression analysis was performed to identify the factors. A total of 357 Bangladeshi women participated in the survey and 55.7% declared they would prefer normal vaginal delivery (NVD) and 37.3% had no clear preference. The actual scenario was the overall CS rate was 51.8% during 2015-2019. But it was very high (77.8%) for the 40 years and above women. The study revealed several important factors that significantly affect the increasing rate of CS for childbirth. Maternal age, religion, current place of residence, working status, monthly household income, birth order, marital age and year of childbirth were found to have significant effect on the high rate of CS. All those who have had face CS at least once in our study faced various problem, they reported. Most of them was feeling tired to do little work and suffered long term back pain. This study will help policy makers in formulating appropriate programs to cope with this challenge efficiently and effectively. Some Special programs should be taken to increase the social awareness and values to save both mother and child, which may lead to decrease the rate of CS in Bangladesh.